HUMAN FACTORS FOR SAFETY IN THE RAILWAY INDUSTRY REVIEW - Ndonwie Frank Emmanuel Fonchang (International Journal of Innovations in Engineering Research and Technology, 2021)
In the railway industry, the human factor for safety has become a serious issue because, the high cost of energy on roads and airplanes, rising energy costs with scarcity, and a desire to decrease pollution have necessitated a switch from vehicle to rail transportation. That being the case, the congestion on the railway has led to numerous accidents pushing many researchers to address several issues regarding work place safety, cognitive problems, reliability, Availability and maintainability safety RAMS. This paper presents the literature study on the human factors for safety in the railway industry using requirement engineering (RE) processes for gathering information needed to optimize sustainable railway operation. Additionally, early traditional models for human reliability analysis (HRA) and railway standards were developed to solve human errors arising from these man-made systems as delineated in this work. Apart from some traditional HRA generation models which are unable to solve complex human-machine problems, a third generational model has been developed to handle such task because of its dynamic modelling system. Finally, the railway operation system necessitates a huge number of stakeholders and individuals, which leads to more human errors and, as a result, serious consequences.